The Effect of Chronotropic Incompetence on Physiologic Responses During Progressive Exercise in People with Parkinson’s Disease - Benevides Panassollo, Tone Ricardo; Lord, Sue; Rashid, Usman; Taylor, Denise; Mawston, Grant (Springer, 2024)
PURPOSE: Heart rate (HR) response is likely to vary in people with Parkinson's disease (PD), particularly for those with chronotropic incompetence (CI). This study explores the impact of CI on HR and metabolic responses during cardiopulmonary exercise test (CPET) in people with PD, and its implications for exercise intensity prescription. METHODS: Twenty-eight participants with mild PD and seventeen healthy controls underwent CPET to identify the presence or absence of CI. HR and metabolic responses were measured at submaximal (first (VT1) and second (VT2) ventilatory thresholds), and at peak exercise. Main outcome measures were HR, oxygen consumption (VO2), and changes in HR responses (HR/WR slope) to an increase in exercise demand. RESULTS: CI was present in 13 (46%) PD participants (PDCI), who during CPET, exhibited blunted HR responses compared to controls and PD non-CI beyond 60% of maximal workload (p ≤ 0.05). PDCI presented a significantly lower HR at VT2, and peak exercise compared to PD non-CI and controls (p ≤ 0.001). VO2 was significantly lower in PDCI than PD non-CI and controls at VT2 (p = 0.003 and p = 0.036, respectively) and at peak exercise (p = 0.001 and p = 0.023, respectively). CONCLUSION: Although poorly understood, the presence of CI in PD and its effect on HR and metabolic responses during incremental exercise is significant and important to consider when programming aerobic exercises.
Keywords: Cardiopulmonary exercise test; Exercise prescription; Heart rate; Oxygen consumption; Cardiopulmonary exercise test; Exercise prescription; Heart rate; Oxygen consumption; 42 Health Sciences; 4207 Sports Science and Exercise; Physical Activity; Neurosciences; Clinical Trials and Supportive Activities; Parkinson's Disease; Brain Disorders; Clinical Research; Aging; Neurodegenerative; 2.1 Biological and endogenous factors; Neurological; 1106 Human Movement and Sports Sciences; Sport Sciences; 3202 Clinical sciences; 3208 Medical physiology; 4207 Sports science and exercise; Humans; Parkinson Disease; Male; Female; Heart Rate; Oxygen Consumption; Middle Aged; Aged; Exercise; Exercise Test; Humans; Parkinson Disease; Exercise Test; Exercise; Oxygen Consumption; Heart Rate; Aged; Middle Aged; Female; Male; Humans; Parkinson Disease; Male; Female; Heart Rate; Oxygen Consumption; Middle Aged; Aged; Exercise; Exercise Test